Faktor-Faktor Yang Memengaruhi Kinerja Keuangan Pasca Pandemi Covid-19 : Studi Empiris Pada Perusahaan Kesehatan Di Indonesia Dan Malaysia - Roza Novita Purnamasari; Mahameru Rosy Rochmatullah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to compare the factors influencing financial performance between healthcare companies in Indonesia and Malaysia post-COVID-19. This quantitative research utilized samples from the annual reports of healthcare companies in Indonesia listed on the Indonesia Stock Exchange (IDX) and the annual reports of healthcare companies in Malaysia published on their official websites for three consecutive years (2020-2022). Out of a population of 44 healthcare companies in Indonesia and Malaysia, 28 companies met the criteria as samples, comprising 15 healthcare companies in Indonesia and 13 in Malaysia. Purposive sampling method was employed. Regression panel data analysis using Eviews 12 revealed that leverage, approximated by Debt to Asset Ratio (DAR), and intellectual capital, measured by Value Added Capital Employed (VACA), significantly influenced the financial performance of healthcare companies in Indonesia. However, Debt to Equity Ratio (DER), Structural Capital Value Added (STVA), and Total Asset Turnover (TATO) showed no significant impact on financial performance. Conversely, in Malaysian healthcare companies, intellectual capital (VACA) and TATO were identified as influential factors on financial performance, while leverage (DAR and DER) and intellectual capital (STVA) did not significantly affect financial performance. Keywords: Financial Perfomance, Debt to Asset Ratio, Debt to Equity Ratio, Value Added Capital Employed, Total Asset Turnover